2022
DOI: 10.3233/shti220132
|View full text |Cite
|
Sign up to set email alerts
|

Using a Wearable Device and Patient Reported Outcome to Evaluate the Influence of Sleep on Quality of Life Among Breast and Prostate Cancer Patients

Abstract: Few studies have used the combination of subjective and objective measures to investigate sleep problems as a primary outcome of concern in cancer patients. This study highlights the influence of sleep quality and duration on quality of life among breast and prostate cancer patients. Thirty-one participants were included in this study. Sleep quality and duration was assessed using a wearable actigraphy device and Pittsburgh Sleep Quality Index questionnaire. Quality of life was measured by European-Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chan et al found a dyadic association between psychological distress and sleep disturbance among Chinese patients with cancer and their spouses [ 7 ], which is similar to our study. Dhar et al implied that breast cancer patients who were poor and short sleepers showed greater deficits in QoL [ 13 ]. Our study also estimated that sleep quality has a positive correlation with the QoL, and both can be improved by the CALM intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al found a dyadic association between psychological distress and sleep disturbance among Chinese patients with cancer and their spouses [ 7 ], which is similar to our study. Dhar et al implied that breast cancer patients who were poor and short sleepers showed greater deficits in QoL [ 13 ]. Our study also estimated that sleep quality has a positive correlation with the QoL, and both can be improved by the CALM intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have used commercial wearables to measure sleep in clinical trials among cancer patients 28 , 29 . Research is also expanding to explore the potential role of these sleep trackers in measuring sleep in comparison to traditional sleep diaries.…”
Section: Discussionmentioning
confidence: 99%